Faktor Yang Mempengaruhi Flame Cutting CNC Dan Waktu Pendinginan Terhadap Kekerasan - Mustafa, Mustafa; Sudarno, Sudarno (LPPM Universitas Merdeka Madiun, 2021)
Abstractâ€” In material that is subjected to heat treatment or workmanship such as in the welding process or flame cutting cutting, it will experience structural changes and mechanical properties. Changes in mechanical properties will cause losses such as: material becomes hard and brittle, although tensile strength and wear resistance increases. In this study an analysis of the factors affecting flame cutting cnc and cooling time against hardness was carried out. This study aims to determine the factors that influence the change in hardness on the results of flame cutting cutting. The study was conducted with three different treatments. The results of flame cutting cutting are cooled with 10 seconds, 25 seconds and 50 seconds respectively. Hardness data collection was carried out at a distance of 2 mm, 10 mm, 20 mm, 30 mm, 40 mm and 50 mm. The experimental results showed that the hardness value of SS 400 material at 10 seconds cooling time resulted in an average hardness of testing 1 = 76 HRB, testing 2 = 76 HRB, testing 3 = 76 HRB. At 25 seconds cooling time produces the average hardness from testing 1 = 74.83 HRB, testing 2 = 74.66 HRB, testing 3 = 74.33 HRB. And the 50-second cooling time produces the average hardness of the test 1 = 73.66 HRB, testing 2 = 73.33 HRB, testing 3 = 7658 HRB.Â Keywordsâ€”: flame cutting; SS 400; hardness.